Microwave and RF engineering - Sorrentino, Roberto (Microwave and Optical Engineering., 2010)
An essential text for both students and professionals, combing detailed theory with clear practical guidance. This outstanding book explores a large spectrum of topics within microwave and radio frequency (RF) engineering, encompassing electromagnetic theory, microwave circuits and components. It provides thorough descriptions of the most common microwave test instruments and advises on semiconductor device modelling. With examples taken from the authors€ own experience, this book also covers: network and signal theory; electronic technology with guided electromagnetic propagation; microwave.